PERANCANGAN APLIKASI E-LEARNING BERBASIS ANDROID PADA SMP TERPADU AL-QODIR - Syafitri, Desy Nurul; Sudewi, Sudewi (YHMM PUBLISHING, 2023)
Due to the Covid-19 pandemic that has hit all countries, especially Indonesia, home study programs have been implemented to avoid transmission of Covid-19. To comply with these regulations, learning is replaced with online/in-network so that students continue to get lessons that should be obtained at school, but students are still protected from transmission of Covid-19. In online learning at the Al-Qodir Integrated Middle School there are several problems that arise Because the Al-Qodir Integrated Junior High School still uses WhatsApp media, which is deemed inaccurate and efficient, the problem that usually arises is that the material that has been sent by the teacher council is deleted due to accidental or too much material that has been sent, causing confusion. Therefore, the author aims to create an Android-based e-learning application. The method used for system development is the waterfall method. While the method used for designing and developing applications is the UML method. The result achieved is a learning application that is easy to use, has a simple display, and is also lightweight for low and low smartphones. With this application, it is hoped that it can facilitate learning at home, besides that it can also help teachers in the process of delivering material and student assignments easily and efficiently